(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
The present study investigates the flow and heat transfer characteristics of a bi-dimensional planar corrugated channel. Computational fluid dynamics is used to study the effect of Reynolds number \((2000=Re=4000)\) and two different values of channel height 5 and 10 mm on the heat transfer and flow developments. The obtained results are validated by comparing with the experimental data and there is a good agreement.